PERAN PEMIMPIN DALAM KEGIATAN KEPRAMUKAAN DI UNIVERSITAS RIAU - Abdalla, Abdi; Sadad, Abdul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The Role of Leaders in Scouting Activities in Riau Univercity face some problems such as confusing information and lack of collaboration whether internal or external activities. The formulation of this research is how is the Role of Leaders in Scouting Activities in Riau Univercity and what factors that become obstacle of Leader's Role in Scouting Activity in Riau Univercity. The purpose of this research is to determine the factors that inhibit the Role of Leaders in Scouting Activities in Riau Univercity. This research used the theory of Oemar Hamalik about five things that need to be considered for the role in organization led, include : catalyst, facilitator, problem solver, source link, and communicator. This research method is used qualitative descriptive approach. Then, the informant in this research is the chairman of clusters, builders, and head of scouts Riau Univercity. The data collection techniques in this research are interviews, observation, and documentations. The result of this research is the Role of Leaders in Scouting Activities in Riau Univercity is running in accordance with existing procedures that is through deliberation and consensus in solving problems. Another way are communicating with coaches, learners, and relevant agencies to establish cooperation in every carry out activities. So that, the activities can be carried out smoothly. Factors that hamper the Role of Leaders in Scouting Activities in the form of participation of some coaches and learners, as well as limited budget funds and not sufficient. Keyword : Role of Leaders, Activities, and Scouting